2019
DOI: 10.24953/turkjped.2019.06.017
|View full text |Cite
|
Sign up to set email alerts
|

A case of craniopagus parasiticus: an antenatal diagnosis by ultrasound screening at 16 weeks of gestation and a literature review of recently reported cases

Abstract: Fahdi BS. A case of craniopagus parasiticus: an antenatal diagnosis by ultrasound screening at 16 weeks of gestation and a literature review of recently reported cases. Turk J Pediatr 2019; 61: 941-945. Craniopagus parasiticus (CP) is a rare type of malformation of conjoined twins, with one degenerated or underdeveloped parasite twin united at the cranium with the other fully developed twin. Only a handful of cases have been documented in the literature to date. The incidence of this rare deformity is approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…It has been reported that 89% of cases are detected before 18 months of age [15], possibly due to the disease's tendency to develop in late gestation, making it rarely detectable during routine screening in the second trimester. Prenatal ultrasound examination is the best method for diagnosing a FIF during pregnancy [16,17], highlighting the importance of regular prenatal check-ups.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 89% of cases are detected before 18 months of age [15], possibly due to the disease's tendency to develop in late gestation, making it rarely detectable during routine screening in the second trimester. Prenatal ultrasound examination is the best method for diagnosing a FIF during pregnancy [16,17], highlighting the importance of regular prenatal check-ups.…”
Section: Discussionmentioning
confidence: 99%